2020
DOI: 10.1111/ans.16241
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in abdominal exudate and serum predict small bowel obstruction following appendectomy

Abstract: Background: This study aimed to investigate the value of inflammatory markers for the prediction of small bowel obstruction (SBO) following appendectomy. Methods: We included cases of acute appendicitis that underwent laparoscopic appendectomy (LA) in the Qingdao Municipal Hospital between January 2017 and January 2019. The cases were divided into an SBO group and a non-SBO group depending on whether patients had or did not have SBO, and patients were followed up for at least 1 year. The levels of interleukin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…J. Rocha et al [13] investigated the anti-inflammatory effects of rosmarinic acid on thermal injury and found that rosmarinic acid significantly reduced TNF-α level in the blood versus control. According to Ding et al [6], IL-6 and TNF-α in serum and abdominal exudate played an important role in the development of small bowel obstruction after laparoscopic appendectomy. Peritoneal IL-6 was the most reliable prognostic marker of small bowel obstruction.…”
Section: Discussion Of the Researchmentioning
confidence: 99%
“…J. Rocha et al [13] investigated the anti-inflammatory effects of rosmarinic acid on thermal injury and found that rosmarinic acid significantly reduced TNF-α level in the blood versus control. According to Ding et al [6], IL-6 and TNF-α in serum and abdominal exudate played an important role in the development of small bowel obstruction after laparoscopic appendectomy. Peritoneal IL-6 was the most reliable prognostic marker of small bowel obstruction.…”
Section: Discussion Of the Researchmentioning
confidence: 99%